Structure-activity relationships for dipeptide prodrugs of acyclovir - Santos, Cledir R. (2015)
A series of water-soluble dipeptide ester prodrugs of the antiviral acyclovir (ACV) were evaluated for their chemical stability, cytotoxicity, and antiviral activity against several strains of Herpes Simplex-1 and -2, vaccinia, vesicular stomatitis, cytomegalovirus and varicella zoster viruses. ACV dipeptide esters were very active against herpetic viruses, independently of the rate at which they liberate the parent drug. Their minimum cytotoxic concentrations were above 100 mu M and the resulting MCC/EC50 values were lower than those of ACV. When comparing the reactivity of Phe-Gly esters and amides (ACV, zidovudine, paracetamol, captopril and primaquine) in pH 7.4 buffer it was found that the rate of drug release increases with drug's leaving group ability. Release of the parent drug from Phe-Gly in human plasma is markedly faster than in pH 7.4 buffer, thus suggesting that the dipeptide-based prodrug approach can be successfully applied to bioactive agents containing thiol, phenol and amine functional groups. (C) 2008 Elsevier Masson SAS. All rights reserved.. - Funda Ao para a Ciencia e Tecnologia (Portugal) ; CIQUP (PG) ; [SFRHBD/9277/2002]. - Thanks are due to Funda Ao para a Ciencia e Tecnologia (Portugal) for financial support through plurianual funding of research units CIQUP (PG), iMed.UL (RM) and through doctoral grant SFRHBD/9277/2002 (CRS). The authors also thank MEDINFAR for kindly offering acyclovir.